Acanthosis nigricans in association with congenital adrenal hyperplasia: resolution after treatment. Case report - Kurtoğlu, Selim; Atabek, M Emre; Keskin, Mehmet; Canöz, Ozlem (The Turkish Journal of Pediatrics, 2005)
A case is described of a three-day-old female with salt wasting type of 21-hydroxylase deficient congenital adrenal hyperplasia who presented with acanthosis nigricans of both axillae. Following corticosteroid and mineralocorticoid therapy for disease, the acanthosis nigricans resolved. It is believed that this is the first reported case of acanthosis nigricans occurring in association with congenital adrenal hyperplasia, a phenomenon that resolved after treatment. We speculate that the acanthosis nigricans resulted from hyperandrogenemia or other unknown factors in our patient.